Enlargement of the European Union ... an historic opportunity - TYRPENOU (Α.Ε.ΤΥΡΠΕΝΟΥ), A. E. (Journal of the Hellenic Veterinary Medical Society, 2017)
Enlargement is one of the most powerful political tools of the European Union and the driving force which has helped in the transformation of the Central and East Europe. From the moment it was created in 1950 is continuously enlarging and has recendy inspired ambitious reformations for Turkey, Croatia and West Balkans. Its founder members call the people of Europe which put their ideas and unified their efforts. Since that time and according to the article 49 of the European Union, it has been grown up from the 6 initial states to 9, 10, 12, 15 and recently to 25. The process still goes on today with new candidate countries, such as Bulgaria and Romania and with accession negotiations with Turkey just as this country could meet the political criteria for accession and the respect of human rights. On completion of this phase the European citizens could live and work in an extended area beyond the Baltic Sea to the Black Sea and from Nicosia to Kiruna and could work under standard procedures in the biggest and without borders market of the world. Also, they will benefit from their neighbours, who have stable democracies and good market economies. It is a careful procedure for the transition of the countries involved, dispersing peace, stability, well being, democracy, human rights and a state of justice in the whole Europe. Further, when our children will become grownup, they will live in a European Union consisted of thirty or more states and with more than twenty languages, a unique polymorphic culture embracing more than 500.000.000 people.